Selecting the Best Site for Establishing a Nature Reserve Using the AHP Model in Raparin District (Raparin Journal of Humanities (RJH), 2026)
Nature Reserves are considered one of the most important tools for protecting the Environment and preserving wildlife and Biodiversity, Especially in areas with unique Ecological characteristics. The emergence of Environmental problems in a dangerous way has led to several Methods, The establishment of natural reserves is one of the best ways to combat these problems.This study aims to shed light on the status of natural and human resources for establishing a nature reserve in the Raparin area of Sulaymaniyah Governorate, As well as the challenges facing its establishment and development. The study also highlights the importance of the study area's Geographical location and its environmental features, Which can serve as the starting point for such a reserve. The study employed a descriptive-analytical approach, utilizing fieldwork data, Quantitative tools, and satellite imagery. One of the most effective site selection methods for establishing nature reserves, The Analytic Hierarchy Process (AHP), was applied. The results revealed that the area has significant potential, with the 'Highly Suitable' and 'Suitable' categories accounting for 41.13% and 24.4% of the land, Respectively. The 'Moderately Suitable' category covers 12.30%, While 'unsuitable' areas constitute only 5.8%.